Macroeconomics of Migration in New Member States - Bems, Rudolfs (IMF Working Papers; Working Paper ;, 2008)
This paper examines the macroeconomic impact of migration on income convergence in the EU's New Member States (NMS). The paper focuses on cross-border mobility of labor and examines the implications for policymakers with the help of a general equilibrium model. It finds that cross-border labor mobility provides ample benefits in terms of faster and smoother convergence. Challenges, however, include containing wage pressures and better mobilizing and utilizing resident labor that does not cross borders.